Aerobic Photooxidative Carbon–Carbon Bond Formation Between Tertiary Amines and Carbon Nucleophiles Using 2-Chloroanthra-9,10-quinone - Yamaguchi, Tomoaki; Nobuta, Tomoya; Tada, Norihiro; Miura, Tsuyoshi; Nakayama, Tatsushi; Uno, Bunji; Itoh, Akichika (Synlett, 2014)
Carbon–carbon bonds were formed between tertiary amines and carbon nucleophiles such as nitroalkanes, ketones, trimethylsilyl cyanide, or indole under aerobic photooxidative conditions by using 2-chloroanthra-9,10-quinone as an organocatalyst. This reaction uses harmless visible-light irradiation with molecular oxygen as the terminal oxidant.
Keywords: carbon–carbon bond formation; organocatalysis; photooxidation; amines